POTENSI UMBI UWI ( Diocorea alata L) TERHADAP KEMATIAN TIKUS MENCIT PUTIH - Ngadu Adu; Cokorda Javandira; Putu Lasmi Yuliyanthi Sapanca (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This research entitled "the potential of uwi tubers (Dioscorea alata L) against white mice rats". The aim of this research was to determine the potential of uwi tubers to eradicate rats or other plant pests. This research was conducted over a period of two months starting from January 2021 to February 2021, to test the effect of uwi tubers, a randomized block design method (RBD) was used with six treatments, namely treatment (P0) as a control without giving uwi tubers, treatment one ( P1) by giving 5 grams of uwi tubers, treatment two (P2) by giving 10 grams of uwi tubers, treatment three (P3) with giving 15 grams of uwi tubers, treatment four (P4) with giving 20 grams of uwi tubers and treatment five (P5) with the provision of 25 grams of uwi tubers, and each treatment was repeated four times so that the total number of treatments became 24. In testing the potential of uwi tubers (dioscorea alata L) against white mice, uwi tubers with 15 grams in treatment three (P3) gave good results good compared to other treatments indicated by the average number of weight loss in rats, namely 17.75 gram